Faktor-Faktor yang Mempengaruhi Non Performing Financing (NPF) pada Bank Umum Syariah yang Terdaftar di Otoritas Jasa Keuangan (OJK) Periode 2015-2019 - Nensi Yuniarti Zs; Budi Astuti; Furqonti Ranidiah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Non Performing Financing (NPF) is a channeling of funds carried out by financial institutions such as Sharia Banks where in the implementation of financing payments by customers there are things such as non-current financing, financing where debtors do not meet the promised requirements, and the financing does not comply installment schedule. This study aims to determine the effect of internal and external factors on Non-Performing Financing (NPF). Internal factors include Allowance for Impairment Losses (CKPN) and Operating Expenses for Operating Income (BOPO); Macroeconomic factors include Gross Domestic Product and Inflation. Data collection techniques in this study are documentation in the form of quarterly financial statements of Islamic banks and statistical data for the 2015-2019 period. Data analysis techniques used are descriptive analysis test, classic assumption test, multiple regression test, and hypothesis testing. The results of the study show that: (1) Allowance for Impairment Losses (X1) affects the Non Performing Financing (NPF) with a sig value of 0,000 (0,000 <0.05). Operating Expenses Against Operating Income (X2) does not significantly influence the Non Performing Financing (NPF) with a sig value of 0.763 (0.763 > 0.05). Gross Domestic Product (X3) does not significantly influence the Non Performing Financing (NPF) with a sig value of 0.554 (0.554> 0.05). Inflation (X4) does not significantly influence the Non Performing Financing (NPF) with a sig value of 0.001 (0.001< 0.005).